COVID-19 and the Fourth Estate: Asian American Journalists' Gendered Racial Harms and Racial Activation During the COVID-19 Pandemic. (March 2022) - Oh, David C.; Min, Seong Jae
Through in-depth interviews, this study explored the voices of Asian American journalists who faced unprecedented stresses due to the racist discourse of Asian Americans as carriers of disease during the coronavirus disease 2019 (COVID-19) pandemic. Socialized to de-emphasize their vulnerabilities in their professional work, Asian American reporters generally claimed they did not experience racist harms, but further probing revealed indirect harms. Women reporters discussed internalized harms such as elevated anxiety and fear, whereas men reporters referenced only external harms such as racial microaggressions. Women reporters also manifested greater self-reflexivity. The importance of analyzing race and gender in White masculine newsrooms is discussed.